Using Antconc Software in Analyzing Modality: Case Study in EFL Tertiary Students’ Hortatory Exposition Text in Indonesia - Cahyati, Nafilah; Sinar, T. Silvana; Yusuf, Muhammad (LingPoet: Journal of Linguistics and Literary Research, 2021)
This study aimed to analyze the modality and how its realization in argumentative genre texts “ hortatory exposition collected from the students of English Department of USU batch 2018 class B to depict the students writing ability from the perspective of modality. The subjects of this study are the students who already taken four semester of college as writing subject is taught for four semesters. Moreover, the argumentative genre is taught in the semester four based on syllabus. This study used the framework of writing genre-based (Martin, 1984)and Systemic Functional Grammar (Halliday&Matthiessen, 2014). The methodology of the analysis is corpus-based employing software AntConc 3.4.5 by Laurence Anthony in order to generate accurate data of lexical items contain in the texts. The findings showed that modalization type of modality indicating probability is dominantly used by the students as much as 60,08%, otherwise usuality is measly used as it is found only 4.44%. The study also revealed almost three-quarters percent of the modality found are realized as modal operators as it is found 70.68% from the analysis.